Unusual and aggressive course of giant cell-rich osteosarcoma of femur: A case report - Mishra, Pankaj Kumar; Baduke, Anil; Khare, Anshul; Kumar, Vivek; Kori, Vivek Kumar; Gaur, Sanjiv (Indian Journal of Case Reports, 2020)
Primary tumors of bones are rare and composed of around 0.2% of the total load of tumors in humans. Among primary tumors, osteosarcoma is the most common primary non-hematopoietic malignancy. Giant cell-rich osteosarcoma (GCRO) is a rarest histologic variant and comprised of only 1–3% of the total burden of conventional osteosarcoma. Here, we present the case of a 16-year-old female patient with complaints of pain in the left distal thigh for 3 weeks and swelling for 1 week. The X-ray showed the lytic lesions, with a wide zone of transition over the meta-diaphyseal distal femur with a pathological fracture in the supracondylar area and Codman’s triangle. Further investigation revealed the diagnosis of GCRO with the proximal tibia and lung metastasis. The prognosis was explained and radical amputation was planned in the form of above-knee amputation. However, in the post-operative period and before the commencement of the adjuvant therapy, the patient became dyspneic and her Glasgow coma scale started deteriorated and unfortunately, she could not be revived.